A new optical Nova in M31 - Burwitz, V.; Hatzidimitriou, D.; Stefanescu, A.; Steinle, H.; Pietsch, W.; Manousakis, A.; Reig, P.; Papamastorakis, G.; Cikota, S.; Cikota, A.; Sanchez, S. (The Astronomer's Telegram, 2007)
We report the discovery of a optical nova in M31 on four consecutive dithered R filter CCD images obtained on (2007 July 19.00741, 19.00890, 19.01041, 19.01193, with corresponding R magnitudes of 18.8, 18.7, 18.8, 18.5) obtained at the 1.3m Ritchey Chretien f/7.5 telescope at Skinakas Observatory, Crete, Greece, using an Andor DZ436-BV CCD Camera (with a Marconi 2k x 2k chip with 13.5Âµm sq. pixels).
Keywords: Novae; Optical